Perlindungan HAM dalam Masyarakat Bernegara - Sri Hastuti Puspitasari (Fakultas Hukum Universitas Islam Indonesia, 2000)
Asits characteristics of legal nation (the rule oflaw), human rights protection for societies is obligatory for a nation. Government as the holder of political authority on the basis of legal agreement and legitimacy can enforce an intervention, in the form of: firstly: keeping a functional relation between nation and its citizens; secondly, actively involving in avoiding social conflict vertically or horizontally. Institutionalizing the human rights protection towardsthe state policy is intended to widen its essential values and meaning of which it is a fundamental human right.